Promoting health diplomacy in the fight against COVID-19: the case of Vietnam - Tinh,Le Dinh (2022)
Abstract The global but uneven course of the Covid-19 pandemic highlights the importance of international cooperation and negotiation on such matters as financial assistance, medical equipment provision, vaccine development and distribution, and other pandemic response measures. This article will present a theoretical overview of “health diplomacy” and analyze the case of Vietnam within this framework, showing how the country’s political response to the pandemic demonstrates an increasingly proactive engagement in health diplomacy. The article argues that health diplomacy will become more relevant for international relations in the time to come and that the case of Vietnam might yield valuable lessons.